2010
DOI: 10.1016/j.astropartphys.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of Townsend avalanche for negative molecular ions

Abstract: Time projection chambers drifting negative ions (NITPC) instead of electrons have several advantages. A NITPC can operate at very high reduced drift fields without diffusion runaway, and the readout digitization sampling rate requirement is considerably relaxed due to the low drift speed of negative ions. The initiation of Townsend avalanches to allow gas gain in these devices has not been understood until now. It is shown here that the avalanche in low pressure CS 2 vapor is most likely initiated by collision… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Previous works have shown that gas gains greater than 1000 can be achieved in electronegative gases with proportional wires [69], GEMs [70], and bulk Micromegas (Micro Mesh Gaseous Structure) [71]. In contrast to electron gases where only moderate electric fields of order 100 V·cm −1 Torr −1 are needed to accelerate electrons to energies close to the ionization potential of the gas, electronegative gases require much higher electric fields to initiate avalanche even though the electron affinity is usually much lower than the ionization poten- (b) 55 Fe energy spectrum after background subtraction Figure 11 tial [72]. For CS 2 , measurements show that the minimum reduced field, (E/p) min , needed to initiate avalanche is over one order of magnitude larger than for the electron drift gas P10 (10% methane in argon) [72].…”
Section: Gas Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have shown that gas gains greater than 1000 can be achieved in electronegative gases with proportional wires [69], GEMs [70], and bulk Micromegas (Micro Mesh Gaseous Structure) [71]. In contrast to electron gases where only moderate electric fields of order 100 V·cm −1 Torr −1 are needed to accelerate electrons to energies close to the ionization potential of the gas, electronegative gases require much higher electric fields to initiate avalanche even though the electron affinity is usually much lower than the ionization poten- (b) 55 Fe energy spectrum after background subtraction Figure 11 tial [72]. For CS 2 , measurements show that the minimum reduced field, (E/p) min , needed to initiate avalanche is over one order of magnitude larger than for the electron drift gas P10 (10% methane in argon) [72].…”
Section: Gas Gainmentioning
confidence: 99%
“…In contrast to electron gases where only moderate electric fields of order 100 V·cm −1 Torr −1 are needed to accelerate electrons to energies close to the ionization potential of the gas, electronegative gases require much higher electric fields to initiate avalanche even though the electron affinity is usually much lower than the ionization poten- (b) 55 Fe energy spectrum after background subtraction Figure 11 tial [72]. For CS 2 , measurements show that the minimum reduced field, (E/p) min , needed to initiate avalanche is over one order of magnitude larger than for the electron drift gas P10 (10% methane in argon) [72]. A similar study can be done for SF 6 , but we leave this for the future and instead focus on gas gain in this section.…”
Section: Gas Gainmentioning
confidence: 99%
“…Generation of a Townsend avalanche in the MWD requires detachment of the ionization electrons from the negative ions. This occurs in a strong electric field of the micro-well by collision of the negative ion with the gas molecules [68]. The free electrons are then accelerated in the micro-well producing the avalanche.…”
Section: Single Ionization Electron Detectionmentioning
confidence: 99%
“…These negative ions then drift in the uniform electric field to the higher field region of the GEM holes. The electric field is strong enough inside the GEM holes to cause collisional detachment of the ions [14]. The liberated electrons are then multiplied and detected as described for the electron TPC.…”
Section: Introductionmentioning
confidence: 99%